Prevalence of wasting and associated factors among children aged 6–59 months in Habro district, Eastern Ethiopia: a cross-sectional study - Tilahun, Sileshi; Roba, Kedir Teji; Roba, Hirbo Shore; Nure, Jemal Ahmed; Sosengo, Teshome; Ayele, Behailu Hawulte; Maruta, Melat B.; Debella, Adera; Eyeberu, Addis; Mussa, Ibsa (Frontiers in Nutrition, 2024)
Background Globally, five million children under the age of five died in 2021. Asia and African countries contributed to 69% and 27.2% of wasting, respectively. In Ethiopia, out of 901 (10.1%) under-five children, 632 (8.1%) were found to be moderately wasted, and 269 (3.0%) were severely wasted. The purpose of this study was to assess the prevalence of wasting and its associated factors among children between the ages of 6 and 59 months in Habro Woreda, Oromia, Eastern Ethiopia. Methods A community-based cross-sectional study was conducted in Habro Woreda from 25 August to 20 September 2020. In total, 306 participants were included in this study through a systematic sampling technique. Data were collected using a pretested structured questionnaire through a face-to-face interview, entered into EpiData version 3.1, and analyzed using SPSS version 25. Predictors were assessed using a multivariate logistic regression analysis model and reported using an adjusted odds ratio (AOR) with a 95% confidence interval (CI). Statistical significance was set at p < 0.05. Results Overall, the prevalence of wasting among children aged 6–59 months in the Habro district was 28%, with a 95% confidence interval [26.5, 32.2%]. Factors such as mothers illiterate [AOR = 3.4; 95% CI: 1.14–10.47], households without latrines [AOR = 2.91; 95% CI: 1.33–6.37], food-insecure households [AOR = 4.11; 95% CI: 1.87–9], households that did not receive home visits [AOR = 4.2; 95% CI: 1.92–9.15], did not eat a variety of food [AOR = 7.44; 95% CI: 2.58–21.45], sick children after discharge from the program [AOR = 6.55; 95% CI: 2.85–15.02], readmitted children [AOR = 3.98; 95% CI: 1.43–15.07], and wasting 3.42 [AOR = 3.42; 95% CI: 1.24–9.45] were factors statistically associated with outcome variables. Conclusion This study noted that the prevalence of wasting among children aged 6–59 months following discharge from the Outpatient Therapeutic Program remains high. Educational status of the mother, availability of a latrine, separate kitchen in the household, household food insecurity, household dietary diversity, home visit, and admission type were significantly associated with wasting of children after discharge from the outpatient therapeutic program. Therefore, efforts that target these factors should be maximized to reduce the occurrence of wasting among children aged 6–59 months after discharge from the outpatient therapeutic program.